DATA MINING PEMBENTUKAN POLA PENGGUNAAN ALAT KONTRASEPSI DENGAN METODE ASSOCIATION RULE - Elisa Hafrida; Febrina Sari; Desyanti Desyanti; Siti Nurjannah (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2020)
Continuous use of contraceptives is a factor influencing the success of the family planning program. As is well known, contraceptives are not necessarily suitable for everyone's condition, therefore women must be able to determine what contraception is suitable for themselves. The problem is that many women find it difficult to decide what contraceptive method to use, apart from a lack of knowledge and information, there is no concept / pattern for choosing a contraceptive device. The purpose of this study is to find patterns of contraceptive use using the Data Mining Association Rule method. The results of the performance of the Apriori Algorithm produce a combination pattern that describes the set of frequent item sets with the highest confidence value, namely 90% In the Rule, if the injectable contraceptive device is 3 months, then the mother's age is 17-35 years. The pattern that is formed is the result of concept formulation, so that this pattern can be used as a reference for prospective acceptors in determining the choice of contraceptives suitable for use.